2016
DOI: 10.2139/ssrn.2740884
|View full text |Cite
|
Sign up to set email alerts
|

Is Being Agreeable a Key to Success or Failure in the Labor Market?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The gender differential for LOC is narrower and less statistically significant, compared to the differentials observed for Achievement Motivation and (four of) the Big Five. The gender-based differentials in personality traits that we observe in our sample of the Australian population generally align with patterns reported in previous studies (Steinmayr and Spinath, 2008;Shekhar and Devi, 2012) and detected among other cultures and nationalities (Costa et al, 2001;Lee and Ohtake, 2016). …”
Section: Gender Differences In Personality Profilessupporting
confidence: 91%
“…The gender differential for LOC is narrower and less statistically significant, compared to the differentials observed for Achievement Motivation and (four of) the Big Five. The gender-based differentials in personality traits that we observe in our sample of the Australian population generally align with patterns reported in previous studies (Steinmayr and Spinath, 2008;Shekhar and Devi, 2012) and detected among other cultures and nationalities (Costa et al, 2001;Lee and Ohtake, 2016). …”
Section: Gender Differences In Personality Profilessupporting
confidence: 91%
“…Also, the relationship between agreeableness and job exploration behaviors might be interfered with by different cultural values. Some studies show that agreeableness significantly contributes to higher annual income in Japan but acts as a penalty in the United States (S. Y. Lee & Ohtake, 2018). This study hypothesizes that agreeableness might have some benefits for job hunting for Latino business students. Neuroticism should be negatively related to career exploration behaviors.Neuroticism represents an individuals' tendency to exhibit unpleasant emotions, such as depression, anxiety, and anger (McCrae & Costa, 1991).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Also, the relationship between agreeableness and job exploration behaviors might be interfered with by different cultural values. Some studies show that agreeableness significantly contributes to higher annual income in Japan but acts as a penalty in the United States (S. Y. Lee & Ohtake, 2018). This study hypothesizes that agreeableness might have some benefits for job hunting for Latino business students.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Researchers should also focus on other variables that could have cultural differences that personality can help explain. For example, Lee and Ohtake (2016) found that agreeableness in Japan was associated with higher levels of annual income, whereas the opposite was true in the United States. It would be interesting to see if these findings hold true for other, less individualistic societies and if the same trend that we found for leader emergence holds true for other constructs, such as compensation.…”
Section: Discussionmentioning
confidence: 99%